The Impact of Teacher Training Programs on Teaching Competency in Inclusive Schools - Nur Hakimah; Qurrota, Neny; Supriyanti, Iin; Taslim Nst, Puli (BASICA, 2026)
This study aims to analyze the impact of teacher training programs on improving teaching competency in inclusive schools based on a literature review over the past ten years. The research method used library research with a literature review approach. Data sources came from articles from reputable international journals and accredited national journals for the 2015–2025 period that discussed teacher training in inclusive education. Data collection techniques were carried out through a Google Scholar search using keywords such as teacher training, inclusive education, and competency, then selected using inclusion and exclusion criteria to obtain 10 relevant articles. Data analysis techniques used thematic synthesis to identify patterns, themes, and main conclusions from various studies. The results showed that teacher training programs have a significant effect on improving pedagogical competency, learning differentiation skills, identification skills for Children with Special Needs (ABK), and the preparation of Individual Learning Programs (PPI/IEP). The most effective training model is ongoing training based on real practice through coaching, mentoring, and lesson study. Conversely, short, theory-oriented training tends to have a limited impact. The success of training is also influenced by the support of school leadership, collaboration between teachers, and the availability of infrastructure. In conclusion, teacher training is a crucial strategy for improving the quality of learning in inclusive schools. Consequently, teacher professional development policies need to be geared toward contextual, sustainable, practice-based training models supported by the school system to ensure optimal inclusive education services for all students.